2007
DOI: 10.1007/s10620-006-9440-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities and Attenuated Expressions of 5-LOX with Red Ginseng in Helicobacter pylori-Infected Gastric Epithelial Cells

Abstract: Our recent studies documented that red ginseng extract (RGE, isolates from steamed and dried Panax ginseng, C.A. Meyer) can inhibit Helicobacter pylori-induced mitogen-activated protein kinase (MAPK) signaling with repressing either nuclear factor (NF)-κB-DNA binding activity or releases of IL-8 and COX-2 in gastric epithelial cells (Dig Dis Sci 50:1218-1227, 2005. We extended the experiment to prove whether RGE influences 5-lipoxygenase (5-LOX) pathway, thereby suppressing the biosynthesis of 5(S)-HETE. The 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Red ginseng extract has inhibitory 5-LOX enzyme activity and LOX-inhibiting action that suppresses inflammation of H. pylori-infected gastric epithelial cells [162] . Epigallocatechin gallate, one of the green tea catechins, showed significant cytoprotective effects against H. pylori associated gastric cytotoxicity [163] .…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…Red ginseng extract has inhibitory 5-LOX enzyme activity and LOX-inhibiting action that suppresses inflammation of H. pylori-infected gastric epithelial cells [162] . Epigallocatechin gallate, one of the green tea catechins, showed significant cytoprotective effects against H. pylori associated gastric cytotoxicity [163] .…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…RGE blocked NOX activity that was enhanced in renal tubular cells exposed to GM. There were several reports demonstrating the antioxidant effect of red ginseng in cancer cells, pancreatic b cells, auditory cells, and gastric epithelial cells, 18,32,37,38 and recent studies showed the attenuation of mitochondrial dysfunction by red ginseng. 39,40 Ginsenoid restored respiratory chain complex activities and aconitase activity in an animal model of focal cerebral ischemia with a decrease in mitochondrial ROS production, 40 suggesting the neuroprotective effect of red ginseng via an integrated process of mitochondrial protection.…”
Section: Effect Of Red Ginseng Extract On Aki H-s Shin Et Almentioning
confidence: 99%
“…To increase eradication rates of first-line therapy, several clinical trials involving extending treatment duration to more than one week, use of higher doses of per protocol (PP), and/or new antibiotics such as quinolones, use of quadruple therapy, or addition of probiotics, vitamin C, bovine lactoferrin, ginseng, wine, garlic, honey, and cranberry have been carried out [11][12][13][14][15]. Previous studies have suggested that Korean red ginseng 1) inhibits H. pylori colonization, 2) exhibits antioxidative and antiinflammatory effects during H. pylori infection, 3) provides efficient restorative action, 4) inhibits expression of genes associated with generation of volatile sulfur compounds (VSCs), and 5) increases eradication rates in addition to attenuating H. pyloriassociated halitosis [16][17][18][19]. Here, we investigated the effects of supplementation of triple therapy with Korean red ginseng on both H. pylori eradication rates and H. pylori-associated halitosis.…”
Section: Efficacy Of Korean Red Ginseng Supplementation On Eradicatiomentioning
confidence: 99%